The Influence of Intensity of Smartphone Use on The Social Interaction of Students - Sabrina Zahra Fajriningtyas; Faiz Naufal Amanullah; Alwi Siregar (Indonesian Journal of Multidisciplinary Sciences (IJoMS), 2024)
The use of smartphones is currently very widely used in society, especially in social media and communicating with interlocutors using smartphone devices. However, despite all the advantages and convenience provided by smartphones, there are several negative impacts on their users, namely reduced face-to-face social interaction. This has resulted in reduced socialization, greetings and concern among the community, especially students at the Faculty of Psychology, Raden Fatah State Islamic University, Palembang. Therefore, the aim of this research is to find out whether there is a significant influence of the intensity of smartphone use on students' social interactions. This research method uses an experimental method with a research design using a one-group posttest design. The sampling technique uses a probability sampling technique, namely by taking 30 random samples of students from the class of 2021 population. The data collection technique uses a Likert scale questionnaire which has been distributed to respondents. The statistical data analysis technique uses the one sample t-test technique. The results of data analysis obtained a significance value (2-tailed) of 0.383, greater than 0.05, so the hypothesis and research objectives were accepted. So, it can be concluded that there is a significant influence of the intensity of smartphone use on the social interaction of students class of 2021, Faculty of Psychology, Raden Fatah University, Palembang.